Efektifitas Pembelajaran Berdiferensiasi Mapel PAI pada Siswa SLB Negeri Sengonagung Purwosari - rifda, rifda Inayah; Achmat Mubarok; M Jamhuri; Achmad Yusuf (STAI Terpadu Yogyakarta, 2024)
Education in Indonesia is increasingly developing along with the times, and so is the curriculum. Sengonagung State Special School is the only educational institution for children with special needs in Purwosari. Quality education is the main foundation for producing quality future generations. Of course, quality education is not only for normal children, those with special needs are also obliged to get a decent education. The development of differentiated learning models is a very relevant solution in improving the quality and quality of learning to improve learning outcomes, especially for children with special needs. This research aims to develop a differentiated learning model specifically designed for children with special needs that is adapted to students' learning styles and interests, especially in Islamic Religious Education subjects. The research method used is qualitative research with a case study approach. Data collection was carried out through interviews with subject teachers, observations during the learning process, and collecting several documentation. The research results show that the development of differentiated learning media can increase learning effectiveness, because it has been adjusted to students' interests and learning styles. Apart from that, of course teachers play an important role in supporting the implementation of the differentiated learning process on a daily basis.